2010
DOI: 10.1002/jor.21265
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in 3D morphology and bony impingement of human hips

Abstract: For the proper diagnosis or treatment of hip joint disorders caused by anatomical abnormalities, the normal hip joint morphology must be studied to understand its influence on the maximum range of motion (ROM) until bony impingement by focusing on gender differences. Acetabular and femoral morphologies were analyzed from 3D CT images of 106 normal hip joints from elderly men (n ¼ 36 joints) and women (n ¼ 70 joints), and measurements of ROM until bony impingement were made in four directions (flexion, extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
119
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 27 publications
9
119
6
1
Order By: Relevance
“…Many studies have investigated the associations between sex and hip anatomy (Table 5) [5,9,17,29,37,46,52] and between the femoral and acetabular parameters measured in this study (Table 6) [1-3, 9, 14, 24, 31, 39, 46, 50, 52, 54]. Our findings agree with most of this literature but do conflict with two studies [2,54] that found no association between femoral and acetabular version (Table 6).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Many studies have investigated the associations between sex and hip anatomy (Table 5) [5,9,17,29,37,46,52] and between the femoral and acetabular parameters measured in this study (Table 6) [1-3, 9, 14, 24, 31, 39, 46, 50, 52, 54]. Our findings agree with most of this literature but do conflict with two studies [2,54] that found no association between femoral and acetabular version (Table 6).…”
Section: Discussionsupporting
confidence: 78%
“…For example, symptomatic dysplasia and excessive femoral anteversion are more common in females [18,20,35,49,54]. In several series of patients with FAI, women with symptomatic impingement had smaller cam deformities [17,20,24,37] but could present with worse preoperative scores for pain and function than men [23]. The associations between these various anatomic factors and how often they occur in a painful hip are unclear but if unaddressed at the time of surgery might explain failed hip preservation surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing interest in 3D-CT as a research tool for the study of bone and joint anatomy and kinematics [1][2][3][4][5]. The resolution of CT is half the voxel size of CT scan [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed that the half of the femoral head included in the fluoroscopic imaging volume would not affect registration accuracy. We considered the location 3 cm above the acetabular roof to be a proper location centered on the ilium, because the diameter of the femoral head ranged from approximately 3.5 cm to 5.5 cm [12,13]. To assess the effect of the femur on CT-3D fluoroscopic matching of the pelvis, we selected the acetabular fossa as the imaging center, since the corresponding fluoroscopic imaging volume included the largest area of the proximal femur compared to that for the other two imaging centers.…”
Section: Discussionmentioning
confidence: 99%
“…Four markers were fixed to the peripheral region of the pelvis, one to each of the following sites: the anterior superior iliac spine (5), pubic tubercle (6), sciatic notch (7), and ischial tuberosity (8). Four markers were fixed to the femoral head and neck, one at each of the following locations: the superior (9), anterior (10), and inferior head-neck junctions (11), and the anterior cortex of the femoral neck (12). Finally, four markers were fixed to the proximal femur, one to each of the following sites: the tip of the great trochanter (13), the base of the lesser trochanter (14), and the anterior (15) and lateral sides of the femoral shaft (16).…”
Section: Methodsmentioning
confidence: 99%